2016
DOI: 10.1039/c6sc01380e
|View full text |Cite
|
Sign up to set email alerts
|

Embedding electron-deficient nitrogen atoms in polymer backbone towards high performance n-type polymer field-effect transistors

Abstract: The low LUMO level and the conformation-locked planar backbone provide polymer AzaBDOPV-2T with electron mobilities over 3.22 cm2 V–1 s–1 tested in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 41 publications
2
78
0
Order By: Relevance
“…The dihedral angle between the NDI block and bithiophene blocks is 40° in PNDI2TEG‐2T, while The PNDI2TEG‐2Tz exhibits a dihedral angle of only 1°. These results indicate an improved molecular planarity after introducing sp 2 ‐N atoms, which is consistent with previous reports …”
Section: Thermoelectric Properties Of Solution‐processed N‐type Conjusupporting
confidence: 93%
“…The dihedral angle between the NDI block and bithiophene blocks is 40° in PNDI2TEG‐2T, while The PNDI2TEG‐2Tz exhibits a dihedral angle of only 1°. These results indicate an improved molecular planarity after introducing sp 2 ‐N atoms, which is consistent with previous reports …”
Section: Thermoelectric Properties Of Solution‐processed N‐type Conjusupporting
confidence: 93%
“…This resulted in P39 having an n‐type mobility of 1.7 cm 2 V −1 s −1 , when using a similar device architecture to Dou et al Replacing the vinylene comonomer with bithiophene ( P40 ) allowed Lei et al to fabricate top‐gate bottom‐contact devices with electron mobilities up to 1.74 cm 2 V −1 s −1 ; impressively, devices that were both fabricated and tested under ambient conditions maintained an electron mobility of up to 1.45 cm 2 V −1 s −1 * . Dai et al reported an identical polymer to P40 , but this time a pyridyl nitrogen was incorporated into the peripherally fused phenyl rings to produce azaBDO ( P41 ) . The nitrogen atom acted to further lower the LUMO, while encouraging a greater degree of backbone planarity.…”
Section: N‐type Organic Semiconductorssupporting
confidence: 62%
“…In order to enhance the electron‐deficient property of the BDOPV unit, Dai et al replaced the benzene ring of the BDOPV unit with a pyridine ring (AzaBDOPV) and copolymerized the modified acceptor unit with bithiophene ( P51 ) . Since the pyridine unit exhibited a strong electron‐withdrawing character, P51 had a LUMO level of −4.3 eV, suitable for efficient electron injection, whereas the P51 ‐based OFET exhibited a μ e value of 3.22 cm 2 V −1 s −1 .…”
Section: Molecular Design Strategies For High‐performance D–a‐conjugamentioning
confidence: 99%
“…In a manner similar to the approach applied to the polymer P51 , Yue et al synthesized an IIG derivative containing sp 2 ‐nitrogen atoms (AzaIIG) and reported copolymer of the AzaIIG unit and the BT unit ( P54 ) at a μ e value of 1.00 cm 2 V −1 s −1 . The resulting polymer, P54 , exhibited a low LUMO energy level of about −4.0 eV owing to the strong electron‐deficient of the AzaIIG unit.…”
Section: Molecular Design Strategies For High‐performance D–a‐conjugamentioning
confidence: 99%